Directive Speech Acts Drive Higher Engagement: A Pragmatic ‎Linguistic Study of Patisserie Brand Captions - Jerry Wilson; Mukhlis Lubis (Yayasan Darussalam Bengkulu, 2026)
This study examines how three types of pragmatic speech acts directive, expressive, and informative are employed in social media captions by international patisserie brands and how these linguistic strategies relate to consumer engagement. Addressing the limited scholarly attention to speech act functions in commercial digital discourse, this research applies Speech Act Theory and a descriptive quantitative approach to analyze 12 purposively selected captions from Instagram, Facebook, and TikTok. The findings indicate that informative speech acts are the most frequently used, while directive speech acts appear to be associated with relatively higher levels of engagement, particularly within TikTok comment interactions. However, this pattern should be interpreted with caution due to the limited sample size. These results highlight the potential persuasive role of directive forms in digital marketing communication. Despite limitations related to sample size and language scope, the study offers theoretical insights into pragmatic patterning in brand discourse and provides practical implications for optimizing engagement-driven content. Future research should expand the dataset and incorporate multimodal as well as cross-linguistic perspectives to deepen the understanding of speech act functions in digital marketing contexts.